Smart boost converter for DC energy source application - Munirah, Ayub (2009)
Basically this project is about the operation of step-up dc-dc boost converter for DC energy source application. The objective of this project is to practice the application of boost converter and DC source energy. It also have it’s purpose in producing a simple control method for maximum power protection by employing a step-up dc-dc boost converter voltage to a certain value and set the limit voltage for the overvoltage protection system application and load protection. The DC source energy application can be obtain from voltage multiplier as power supply circuit. By using the basic principle, we will build the model and get the simulation for the circuit. In other way to generally explain the operation is the boost converter has functioning switch which had to produce the step-up voltage according to the correct design, the voltage will be the input for the overvoltage protection circuit which is used to protect the load. This circuit has variable voltage setting which can be set as the cut-off voltage to stop the excess voltage from damaging the load or equipment. LED power saving are implement as the load for the DC source energy and also have economical purposes in saving power consumption.